2013
DOI: 10.1097/cad.0b013e32835e9743
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caffeic acid phenethyl ester analogues in a modified resistant hepatocyte model

Abstract: We present a study of the chemoprotective effects of two caffeic acid phenethyl ester (CAPE)-related structures: LQM717 and LQM706. The modified resistant hepatocyte model in rats was used to study the chemoprevention of these CAPE analogues, which are inexpensive and easily obtained. In the liver cancer model used, we detected extensive necrosis and lipid peroxidation after 24 h, many altered hepatic foci, putatively preneoplastic lesions with γ-glutamyl transpeptidase staining after 30 days, and liver tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This suggests the potential merit of CAPE in delaying age‐related hepatocellular changes. Macias‐Perez et al showed that CAPE exhibits protection against lipid peroxidation, necrosis, aberrant cell proliferation and p65 activation. Rats under a carcinogenic protocol ( N ‐diethylnitrosamine) showed decreased number of preneoplastic nodules and reduced incidence of liver tumors when pretreated with CAPE.…”
Section: Biological Activities Of Capementioning
confidence: 93%
“…This suggests the potential merit of CAPE in delaying age‐related hepatocellular changes. Macias‐Perez et al showed that CAPE exhibits protection against lipid peroxidation, necrosis, aberrant cell proliferation and p65 activation. Rats under a carcinogenic protocol ( N ‐diethylnitrosamine) showed decreased number of preneoplastic nodules and reduced incidence of liver tumors when pretreated with CAPE.…”
Section: Biological Activities Of Capementioning
confidence: 93%
“…The effects of these compounds on lipid peroxidation are attributed to the direct antioxidant activity (chelating properties and ROS decrease) of CAPE and the indirect antioxidant activity (inhibition of the metabolism or induction of the antioxidant system in the cells) of their analogs. In addition, the three compounds act by decreasing the activation of p53, NFkB activator (apoptosis-related transcription factor, proliferation and cell cycle) (80).…”
Section: In Vitro and In Vivo Studies Of Caffeic Acid In Hepatocarcinomamentioning
confidence: 99%
“…Dietary supplementation of rats, with CA and CAPE (5 mg/kg body wt subcutaneous or 20 mg/kg oral), was shown to inhibit tumor growth in HCC cells (HepG2) and reduce the tumor invasion at a liver metastatic site [91]. Another clinical study [92] has reported a clear chemoprotective effect of CAPE and its analogs (20 mg/kg body wt) against lipid peroxidation and subsequent cell proliferation of hepatic tumors (HCC) in rats.…”
Section: Caffeic Acid (Ca) and Its Estersmentioning
confidence: 99%
“…CA chemoprotective effect on cell proliferation, p56 activation of hepatic tumors (HCC). [92] CA (100 mg/kg) in the rat microbiota CA reduce certain biomarkers that indicate liver injury [96] Carnosic acid (CarA)…”
Section: Phenolic Acid Experimental Conditions Conclusion Of Study/hmentioning
confidence: 99%